Integrating STEAM into Contextual Literature Lessons: Exploring Creativity in Primary School Students - Aprinawati, Iis; Nurmalina, Nurmalina; Pebriana, Putri Hana (Universitas PGRI Yogyakarta, 2025)
Creativity is recognised as a critical skill for 21st-century learners, yet its development remains limited in elementary school literature classes, which are still dominated by conventional and non-contextual teaching methods. This study examines how contextual literature instruction, grounded in the STEAM (Science, Technology, Engineering, Arts, and Mathematics) framework, can foster creativity among primary school students. A quantitative survey method was employed, involving 80 fifth-grade students from a public school in Pekanbaru, Indonesia, who were selected through simple random sampling. Data were collected through a 35-item Likert-scale questionnaire and classroom observations based on five creativity indicators: fluency, flexibility, originality, elaboration, and imagination. Descriptive analysis showed high levels of imagination (84.2%) and active participation (85.4%), with lower outcomes in originality (75.6%) and creative collaboration (77.5%). These results indicate that STEAM-based literature learning effectively promotes student engagement, imagination, and expression, although it still requires strategies to foster individual innovation and teamwork. The study offers practical implications for educators and policymakers, including the need for teacher training in interdisciplinary pedagogy and the development of infrastructure that supports ethical, inclusive, and creative use of technology in elementary education. Keywords: creativity, STEAM, literature learning, contextual learning